The CSI-education effect: Do potential criminals benefit from forensic TV series? - Baranowski, Andreas M. (International journal of law, crime and justice, 2018)
Forensic series have become popular over the last two decades. They have raised the importance of forensic evidence in the eyes of the public (CSI effect). However, it has not been investigated to what extent criminals may learn about forensic evidence through these shows. We used multiple approaches to tackle this potential CSI-education effect. First, we analyzed crime statistics for crime and detection rate. Second, we asked convicted criminals about their impressions about the usefulness of crime shows for covering up a crime. Third, we asked fans of crime series and a control group of non-watchers to slip into the role of a criminal by enacting the cleaning up a murder crime scene. Finally, a sample of 120 subjects had to clean up the scene of a would-be murder using a model. In none of these experiments did we find supportive evidence for the CSI-education effect.